The use of Polystyrene from Ballpen Barrels and Wood Ash as Additives in Making Lightweight Bricks. - Vandon Borela; Jezreel Matthew M. Ancheta; Jerus Cyril P. Bejar; Loureese Mei L. Garcia (Newinera Publisher, 2021)
This study aimed to determine the ability of polystyrene in ballpen barrels of making a brick to be more compacted than the ordinary clay bricks. Polystyrene is a synthetic aromatic hydrocarbon polymer made from the monomer styrene that also makes a brick denser. The Wood ash from burned wood are usually used by the gardeners as a good source of potash. Wood ash has an ability of making the bricks lighter than the usual clay bricks. Additional wood ash is better than coal ash, because coal ash has a dangerous chemicals that may harm human. The goal of this study is to lessen the ballpen barrels and wood ash that are not disposed properly and make this in a creative way. Five test was conducted to determine the potential of polystyrene and wood ash namely water absorption test, drop test, efflorescence test, compressive test and heat resistance test. Based from the data gathered, it concluded that polystyrene from ballpen barrel and wood ash with the ratio of 50% Cement, 25% Wood Ash, 25% Ballpen Barrels is effective additives in production of lightweight